Effects of cyclosporine on adriamycin induced nephropathy - Soares, Vitor A. [UNESP] (Wiley, 1998)
The effect of cyclosporine on adriamycin nephropathy was studied over both short (6 weeks) and long (26 weeks) periods. In the short-term study, cyclosporine was introduced 2 weeks after nephritis induction and in the long-term study, 14 weeks after the first adriamycin injection. The animals with adriamycin nephropathy treated with cyclosporine, studied for 6 weeks, developed proteinuria with increased renal size and glomerular area. The nephrotic animals treated with cyclosporine showed less proteinuria than the nephrotic control animals. There were no differences in glomerular area, creatinine clearance or serum creatinine and kidney weight between the treated nephrotic group and the health control group. The nephrotic animals, studied for the longer period, developed intense proteinuria, decreased creatinine clearance, glomerular necrosis and sclerosis, severe tubulointerstitial nephritis, increased hydroxyproline concentration and tubulointerstitial area. No difference was observed between the nephrotic animals treated with cyclosporine and those not treated. In conclusion, Cyclosporine A reduced proteinuria, glomerular hypertrophy and kidney weight in rats with short-term nephropathy but had no effect on the established nephropathy.
Keywords: Adriamycin-nephropathy; Cyclosporine; Glomerulosclerosis; Nephrotic syndrome; Proteinuria; cyclosporin a; doxorubicin; animal experiment; drug effect; glomerulosclerosis; kidney disease; kidney mass; male; nephrotic syndrome; nonhuman; priority journal; proteinuria; rat